A preliminary study of radioulnar wrist compression in improving patient-reported outcomes of carpal tunnel syndrome - Zong-Ming Li; Emily L. Grandy; Lenicia Jenkins; Carli Norman; James Bena; Juliet Hou; Peter J. Evans; William H. Seitz; C. Kent Kwoh (BMC Musculoskeletal Disorders, 2022)
Abstract Previous studies have shown radioulnar wrist compression augments carpal arch space. This study investigated the effects of radioulnar wrist compression on patient-reported outcomes associated with carpal tunnel syndrome. Subjects underwent thrice-daily (15 min each time 45 min daily) wrist compression over 4 weeks with an additional four weeks of follow-up without treatment. Primary outcomes included Boston Carpal Tunnel Questionnaire symptom and functional severity scales (SSS and FSS) and symptoms of numbness/tingling based on Visual Analog Scales. Our results showed that radioulnar wrist compression improved SSS by 0.55 points after 2 weeks (p < 0.001) and 0.51 points at 4 weeks (p < 0.006) compared to the baseline scale. At the four-week follow-up, SSS remined improved at 0.47 points (p < 0.05). Symptoms of numbness/tingling improved at two and 4 weeks, as well as the follow-up (p < 0.05). Hand motor impairment such as weakness had a lower frequency across carpal tunnel syndrome sufferers and does not significantly improve (p > 0.05). Radioulnar wrist compression might be an effective alternative treatment in improving sensory related symptoms in patients with mild to moderate carpal tunnel syndrome.